Analyse des besoins de formation des mécaniciens automobiles de la Commune de Keur Massar (Dakar, Sénégal) - Salif BALDE; Cheick Ahmed Tidiane DIENG (Revue Hybrides)
This study aims to know the training needs of Automobile mechanics of the Municipality of Keur Massar in Dakar, Senegal. To achieve this objective, we chose a quantitative approach with a questionnaire as data collection tools. This questionnaire was administered on a sample of 132 Mechanics. The results showed that the Mechanics need to be trained in their sector of activity. Finally, we found that the low level of skills of the Mechanics is mainly explained by the absence of a formal structure that they can use to strengthen their capacities.